Urological problems in postmenopausal women - Darewicz, Barbara; Skrodzka, Marta; Kudelski, Jacek (Menopause Review/Przegląd Menopauzalny, 2008)
Menopausal transition in women is correlated with lower quality of life. Decreased oestrogen levels entail dysfunction of many organs and systems. This paper depicts urological problems in perimenopausal women. The authors delineate the influence of oestrogen levels on physiology and pathophysiology of the urinary tract. Risk factors and treatment options of urological dysfunctions (urinary incontinence, recurrent urinary tract infections, symptoms of urgency) in menopausal transition are characterized. Proper diagnostics and therapy of urogenital problems in climacteric women require cooperation between urologists and gynaecologists as well as broadened knowledge of patients and general practitioners.